Preface (Communications in Computational Physics, 2020)
Ru-Shan Wu is a special scientist who has made tremendous contributions in manyfields of geophysics that he has worked on and has had strong impact on several generations of scientists throughout the world. He is appreciated for his contributions to science and for his generous, outgoing and happy personality that make him a role modelfor those who follow in his footsteps. Ru-Shan has sustained high-quality scientific output over the course of his long career. His work is widely recognized for its value andcreativity. He has keen insight into the underlying physics of wave propagation and hecontinues to successfully transform that insight into fundamental advances in our understanding of wave propagation and imaging.